2021
DOI: 10.52131/jee.2021.0201.0013
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tourism, Economic Growth and Environment in Developing Countries

Abstract: The basic purpose of this study is to identify a link concerning tourism, pecuniary expansion, and environmental protection in developing countries. The current research looks at the overall state of emerging economies as well as income comparisons. The study employs the 3sls model. Tourism benefits from economic growth as well. Tourism is attracted by economic prosperity, and tourism will increase tourism. According to the findings, economic growth has a negative impact on the environment, and the environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Thus, it is concluded that there is no lag effect of the dependent variable on the first difference error in the GDP and CO 2 models. Therefore, because the ab(1) and ab (2) tests are met, it can be concluded that the GDP and CO 2 equation models are consistent.…”
Section: Arellano-bond (Ab) Testmentioning
confidence: 92%
“…Thus, it is concluded that there is no lag effect of the dependent variable on the first difference error in the GDP and CO 2 models. Therefore, because the ab(1) and ab (2) tests are met, it can be concluded that the GDP and CO 2 equation models are consistent.…”
Section: Arellano-bond (Ab) Testmentioning
confidence: 92%
“…Another group of research focuses on the effect of tourism on environmental sustainability (Azam et al, 2018;Lee and Brahmasrene, 2016;Paramati et al, 2017;Paramati et al, 2018;Ali et al, 2021;El Menyari, 2021;Liu et al, 2022;Usman et al, 2021). In accordance with these studies, sustainable development should be ensured by implementing prudent public policy where host governments must strive to promote socially and environmentally responsible tourism industries in their respective countries.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Therefore, host nations should not only encourage tourism, but also guarantee that the environmental quality is sustained. In this regard environmentally friendly tourism policies should be established to maintain a positive path towards sustainable development (Ali et al, 2021).…”
Section: Empirical Evidencementioning
confidence: 99%
“…In addition, the results suggest that a two-stage approach is necessary because it provides a more in-depth look at household spending behavior. For example, highly educated families often participate in sports and invest a lot of money [ 11 ]. Zhang et al pointed out that GDP development should be driven from investment demand to consumption demand in a timely manner, and gradually from external to internal, to cultivate consumption power, thereby driving the timely consumption of residents [ 12 ].…”
Section: Related Workmentioning
confidence: 99%